Teaching problem solving: the "Ten Commandments" approach - Matiwane, Noluvuyo (Rhodes University, Faculty of Science, Department of Physics and Electronics)
The evident need for an intervention to help physics students, especially incoming university students, develop their problem-solving skills led to exploring possible curriculum structures to achieve the goal. A modified curriculum structure of the first-year physics course, including explicit teaching of physics problem solving, was developed and implemented at Rhodes University, South Africa, in 2017. First-year physics students learn to solve problems by implementing the "Ten Commandments" of physics problem solving in their solutions, following a three-stage problem-solving framework. Additionally, students attend whiteboard tutorial sessions where they actively practise using the problem-solving framework in their solutions to physics problems with peers in an environment where help is available. Students are explicitly prompted to use the Ten Commandments" during the whiteboard tutorials and not prompted for other assessment tasks. Students' solutions to formative physics assessment tasks (problem sets and tests) in the first semester were examined, problem-solving scores were determined using a problem-solving rubric developed in the department, shifts in attitudes and beliefs about physics and solving problems in physics were measured, and relationships between their problem-solving scores and task performance were evaluated to investigate how students adopted the framework and its implications over one semester. The problems issued to students differed in context and difficulty level; as a result, not all of the "Ten Commandments" were applicable to solve all problems, and different combinations of the commandments were applied to different problems. The explicit use of the problem-solving rubric to mark student problem sets was an indirect prompt for students to use commandments when doing their problem sets. As a result, students attempted to implement more applicable "commandments" (mostly partially correct) in their solutions to problem sets than in tests. Moreover, students' solutions to problems show that they used more of the "commandments" they were familiar with from school and less of the new ones, such as drawing diagrams without being prompted, producing algebraic solutions before substituting numbers, and doing dimensional analysis. Problem sets are often assumed to help prepare students for tests; however, correlations between students' problem-solving scores and performance between the two assessments did not give clear indications of whether problem sets were helping to prepare students to solve problems. Lastly, students' attitudes and beliefs also show a negative shift in students' perceptions of problem-solving by the end of the first semester. Problem-solving is a skill that develops in stages and over time; therefore, a timeframe longer than one semester is needed to report on significant changes in students' problem-solving habits and perspectives about problem-solving in physics. The study results are also important in giving insights into the initial developments of problem-solving skills and teaching problem solving.
Keywords: Problem solving-- Study and teaching; Physics-- Study and teaching; Curriculum change; Rhodes University; College students Attitudes